ความไม่สมมาตรของข้อมูลในการประกันภัยพืชผลของไทย: กรณีศึกษา โครงการประกันภัยข้าวนาปี - ดามพ์ ไข่มุกด์ (จุฬาลงกรณ์มหาวิทยาลัย, 2018)
Natural disasters had caused damages on agricultural yield with an average loss of 7,253 Million Baht/Year. The government has implemented a crop insurance program to help farmers in disaster risk management. However, management system faces significant problems caused by different background of farmers.Asymmetric information could be a major cause of the problem. This study focuses on the problem of asymmetric information that affects farmers’ participation in the program in different risk areas. Data from 379 households of rice farmers are used to analyze the Adverse Selection and Moral Hazard using the Ordered Logit model and the expected return value. Also, the Binary Logit model was used to examine factors that affect farmers’ participation in the program.Results indicate that factors that affect the farmers’ participation in the program are government subsidies and farmer experience of disasters. Adverse Selection and Moral Hazard are different at the area level. Rules and polices partly lead to Asymmetric Information. Therefore, determining appropriate criteria in the context of farmers in each area is important to reduce such problems.